2007
DOI: 10.1080/07370010701429512
|View full text |Cite
|
Sign up to set email alerts
|

Home Health Care Nurses' Perceptions of Empowerment

Abstract: This exploratory study involved the triangulation of qualitative (interview and observation) and quantitative methods (Psychological Empowerment Instrument). This study examined the individual home care nurses' perception of empowerment and how it influences decisions in the home clinical setting. Fifteen nurses were self-selected to participate. All completed an interview, and were observed and given Likert Instrument to complete. A framework analysis was performed to identify mutually exclusive and exhaustiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…This finding is consistent with results of a mixed-method study using the PEI and interviews done by Williamson 14 examining home health nurses' perception of psychological empowerment. PEI scores were high in this study, and interviews of participants identified collaboration as one of the most important facets of empowerment.…”
Section: Relationships Between Moral Distress Empowerment and Demogsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is consistent with results of a mixed-method study using the PEI and interviews done by Williamson 14 examining home health nurses' perception of psychological empowerment. PEI scores were high in this study, and interviews of participants identified collaboration as one of the most important facets of empowerment.…”
Section: Relationships Between Moral Distress Empowerment and Demogsupporting
confidence: 81%
“…The MDS uses 3 factors or subscales to measure moral distress: (1) individual responsibility (refers to the nurse participating in care not agreed with or ignoring actions one should take-20 items), (2) not in patient's best interest (refers to participating built on the work of Jameton. 7 Multiple studies 4,10,[13][14][15][16][17][18] have shown that futile care, where nurses perceived that the patient would not benefit from care, caused the most significant levels of moral distress in nurses.…”
Section: Data Collection (Instruments and Procedure)mentioning
confidence: 99%
“…The way roles and relationships are built, negotiated, and experienced shows the relevance of the relationship between nurses and patients when defining their experiences and perceptions of the quality of care in general (16) . A large part of nursing care in HC is dedicated to active listening to patients, in an effort to comfort them (18) . In one of the studies, nurses were named as the professionals most sensitive to patient demands, which turns the acts of being polite and offering dialog into care strategies, in tandem with conscience and responsibility (20) .…”
Section: Nursing Actions In Home Carementioning
confidence: 99%
“…The HC space requires highly qualified nurses, with various abilities and commitment (33) , who possess a wide range of clinical and care competencies and a high degree of autonomy to conduct their work, performing continuous monitoring of their patients, in chronic or acute conditions, in the family and community spheres, and who employ a balance of curative and preventive actions (33) . In addition, their role in the practice of home care is based on the recognition of their competence regarding their skills, abilities, aptitudes, and experiences (18) . However, concerning challenges inherent to the complexity of nursing practice in home care, it was possible to verify that insufficient training or little experience in HC services (19) and lack of ability and knowledge (28)(29) can negatively influence home care.…”
Section: Necessary Knowledge For Nursing Practice In Home Carementioning
confidence: 99%
See 1 more Smart Citation